Insulin Resistance in firstborn offspring of mother who developed diabetes later in fourth decade: Are both related to possible maternal malnutrition? - Bajracharya, M.R.; Bhattarai, M.D.; Karki, B.B.; Prajapati, S.; Karmacharya, D.; Manandhar, S.; Rajouria, A.D. (Journal of Advances in Internal Medicine, 2015)
Back grounds and Aims: Diabetes mellitus is increasing each day. We aimed to study the insulin resistance (IR) in the offspring of people with diabetes and its relation with lifestyle and clinical factors. Methods: This is a cross sectional study of IR in offspring over the age of 18 years and having parents with diabetes. Participants already diagnosed as having diabetes, suffering from any illness or using drugs that may have altered blood sugar levels were excluded. A fasting blood sample was taken for blood glucose and serum insulin level and IR was calculated using homeostatic model assessment for IR (HOMA –IR). Results: Forty nine participants volunteered for the study of which 24.5% were found to have IR, the cut off value of HOMA –IR being 2.48. As compared to the later born offspring, the firstborn were six times more at risk for IR (Odds ratio 6.25, P value 0.015) and after adjustment for BMI, it was seven times (Odds ratio 7.29 , P value 0.011). IR was more in offspring with maternal diabetes than with paternal one. The mean age of diagnosis of diabetes in mothers having firstborn offspring with IR was 38.5 years as compared to 48.2 years of those having firstborn offspring without IR. Conclusion: Higher risk of IR seen in the firstborn offspring whose mother later developed diabetes at fourth decade indicate the probability of relation of both conditions with possible maternal malnutrition during the first pregnancy. Further larger studies are required focusing on these aspects. Journal of Advances in Internal Medicine 2014;3(2):56-61